Dire l’Europe à travers le monde - Arnaud Brennetot; Karine Emsellem; France Guérin-Pace; Bénédicte Garnier (Cybergeo, 2013)
Thinking about what Europe is, about its location or its limits often consists in trying to identify something such as a European identity, a common project or adherence to a lifestyle. In this perspective, the feeling of belonging to a place implies various dimensions, including subjective perceptions. To explore this, the research project EuroBroadMap and the survey “Visions of Europe”, conducted on a sample of 10,000 students living in eighteen different countries around the world, allows us to enrich our comprehension of these perceptions of Europe. From a set of words spontaneously related to Europe by the students surveyed, the methods of textual statistics enabled us to measure the variety of the vocabulary associated to this place. Several factors may explain the diversity of the words obtained: the students’ academic fields and countries of residence strongly condition the way they perceive Europe. Furthermore, it is noteworthy that belonging to the European Union or to its margins influences the individual perceptions.